The Literary Ecocritism In The Romantic Period Poem “Nachts” By Joseph von Eichendorff - Kasturi, Rayhan Adhya; Dudy Syafruddin (Nexus Publishing NXP, 2024)
Literary works can be a portrait of phenomena that occur in the surrounding nature, both as appreciation and criticism. This research aims to identify the spirit of the times in the poem